2019
DOI: 10.1016/j.kint.2018.11.034
|View full text |Cite
|
Sign up to set email alerts
|

β-hydroxybutyrate attenuates renal ischemia-reperfusion injury through its anti-pyroptotic effects

Abstract: Ketone bodies including b-hydroxybutyrate (b-OHB) have been shown to protect against ischemic tissue injury when present at low concentrations. We evaluated the impact of b-OHB on renal ischemia/reperfusion injury (IRI). Mice were treated with a continuous infusion of b-OHB using an osmotic mini-pump before and after IRI. We also tested the effects of increasing endogenous serum b-OHB levels by fasting. Renal IRI was attenuated by b-OHB treatment compared to saline control, with similar results in the fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 65 publications
(64 reference statements)
3
85
0
Order By: Relevance
“…It forms pores in the plasma membrane that ultimately cause cell swelling, membrane lysis, and inflammatory cytokines release (Shi et al, 2015). GSDMD-mediated pyroptosis of renal TECs is an essential process in renal ischemia-reperfusion (I/R) injury (Diao et al, 2019;Tajima et al, 2019;Liu et al, 2020). Thus, studies are needed to determine the biological networks involved in GSDMD-mediated pyroptosis in TEC injury induced by renal IR.…”
Section: Introductionmentioning
confidence: 99%
“…It forms pores in the plasma membrane that ultimately cause cell swelling, membrane lysis, and inflammatory cytokines release (Shi et al, 2015). GSDMD-mediated pyroptosis of renal TECs is an essential process in renal ischemia-reperfusion (I/R) injury (Diao et al, 2019;Tajima et al, 2019;Liu et al, 2020). Thus, studies are needed to determine the biological networks involved in GSDMD-mediated pyroptosis in TEC injury induced by renal IR.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences have emphasized the importance of HDAC-regulated epigenetic modification in the development of kidney injury (Wang et al, 2014;Ma et al, 2017;Yoshikazu et al, 2018). When exposed to ischemia/reperfusion injury, histone acetylation modification of kidneys was reduced, while b-hydroxybutyrate attenuates kidney injury by restoring histone acetylation at the FOXO3 promoter (Takaya et al, 2019). In addition, targeting histone H4 acetylation via phosphoinositide 3-kinase-and p70s6-kinasedependent pathways could inhibit iNOS production and alleviated injury in glomerular mesangial cells (Yu and Kone, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the t 1/2 of FOXO1 was decreased ( Figure S2A) and protein level of FOXO1 was up-regulated in HK2s exposed to H/ R. The elevated protein levels were due to enhanced transcription of FOXO1. It has been reported that the protein expression of FOXO3 was attenuated in I/R renal tissue and or H/R HK2 cells (Tajima et al, 2019;Wu et al, 2016). Moreover, we only focused on FOXO1 function in renal I/R injury because AS1842856 is a selective inhibitor that blocks the transcription activity of FOXO1 (IC 50 : 33 nM;Nagashima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%